Hubungan Durasi Mengemudi Dan Usia Dengan Keluhan Hemoroid Pada Sopir Bus Di Terminal AKAP (Antar Kota Antar Provinsi) Payung Sekaki Pekanbaru Riau - Annes Waren; Rizki Ramadhan; Nurshal Hasbi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Background : Hemorrhoids is one of the most common anorectal diseases, this disease can cause physical and psychological discomfort due to its disturbing symptoms such as rectal bleeding, pain, and itching sensation and will significantly affect the quality of life of the person with hemorrhoids. According to Slavin (2008), the prevalence of hemorrhoids in the world reaches 5%. There are various risk factors for hemorrhoids, one of which is the length of sitting without changing the position and age. According to Ali and Shoeb (2017) in their research, there were 50 patients out of 60 drivers experiencing hemorrhoids. A driver job that requires a long time to sit because of the long duration of driving can cause hemorrhoids. Kumala, et al (2016) said in their research on intercity and interprovincial (AKAP) bus drivers who have a driving duration of ≥ 6 hours have a risk of hemorrhoids and those aged ≥ 45 years have a risk of developing hemorrhoids.Objective : Knowing the relationship between driving duration and age with hemorrhoids in bus drivers at the AKAP Payung Sekaki terminal Pekanbaru in 2020.Methode : The design used in this study was an observational analytic type with a cross-sectional method. The sampling technique was accidental sampling, with a sample of 60 respondents who had the inclusion criteria. Statistical test data using the Chi-Square test.The results : There was an insignificant relationship between the duration of driving and complaints of hemorrhoids in the driver (p-value = 0.057) and the relationship between age and complaints of hemorrhoids in the driver (p-value = 0.073).Conclusion : There is an insignificant relationship between driving duration and age with complaints of hemorrhoids in bus drivers at AKAP Payung Sekaki Terminal